Topological indices computing on random chain structures. Issue 8 (21st December 2020) - Li, Siman; Shi, Li; Gao, Wei
Abstract: Topological indices are a vital tool in QSAR/QSPR study, and Randić index and Zagreb index are mostly historical and well‐known indices which have been widely used to predict the properties of compounds. In recent years, to meet the demands from various engineering applications, some variants of Randić index and Zagreb index are defined and investigated. In this work, we determine the redefined Zagreb indices, forgotten index, reduced reciprocal Randić index and reduced second Zagreb index for random polyphenyl chain and random spiro chain which are produced by zeroth‐order Markov process and frequently appears in the field of materials and pharmacology. Furthermore, the average values and special settings in p 1 or p 2 to be zero are discussed. Abstract : The random polyphenyl chain and random spiro china are defined by zero‐order Marko process, and there are three types of arrangement in adding a hexagon h n with probability p1, p2 and 1 1 p1 1 p2, respectively. The main contribution of this work is to determine some new version topological indices of these two random chains.